Precise Study on Size-Dependent Properties of Magnetic Iron Oxide Nanoparticles for In Vivo Magnetic Resonance Imaging. (28th May 2018) - Chen, Ling; Xie, Jun; Wu, Haoan; Li, Jianzhong; Wang, Zhiming; Song, Lina; Zang, Fengchao; Ma, Ming; Gu, Ning; Zhang, Yu
Abstract : Developing a biocompatible contrast agent with high stability and favorable magnetism for sensitive detection of malignant tumors using magnetic resonance imaging (MRI) remains a great demand in clinical. Nowadays, the fine control of magnetic iron oxide nanoparticle (MION) sizes from a few nanometers to dozens of nanometers can be realized through a thermal decomposition method of iron precursors. This progress allows us to research accurately on the size dependence of magnetic properties of MION, involving saturation magnetization (M s ), specific absorption rate (SAR), and relaxivity. Here, we synthesized MION in a size range between 14 and 26 nm and modified them with DSPE-PEG2000 for biomedical use. The magnetic properties of PEGylated MION increased monotonically with MION size, while the nonspecific uptake of MION also enhanced with size through cell experiments. The MION with the size of 22 nm as a T2-weighted contrast agent presented the best contrast-enhancing effect comparing with other sizes in vivo MRI of murine tumor. Therefore, the MION of 22 nm may have potential to serve as an ideal MRI contrast agent for tumor detection.